kinkajou26
kinkajou26
14-12-2019
Mathematics
contestada
Simplify the expression
6x-4(x-3)-x
Respuesta :
kalsoomtahir1
kalsoomtahir1
14-12-2019
Answer:
x = -12
Step-by-step explanation:
6x-4(x-3)-x
6x - 4x +12 - x
2x -x +12
x + 12 = 0
x = -12
Answer Link
VER TODAS LAS RESPUESTAS ( 82+ )
Otras preguntas
What were the 4 major truths Jefferson presented in the declaration of independence?
3 ( 4d + 1 ) - 9d = 6 - 2d
What were the 4 major truths Jefferson presented in the declaration of independence?
2 ( 4a - 12 ) + 3a = 6a + 1
how have computers changed mapmaking in recent years
36 is _______% less than 60?
3 ( 4d + 1 ) - 9d = 6 - 2d
what are three ways water erodes the surface of earth
A snowball is launched horizontally from the top of a building at v = 16.9 m/s. If it lands d = 44 meters from the bottom, how high (in m) was the building?
Your model locomotive is 18 inches long. It is an exact model of a locomotive that is 72 feet long. A window on the locomotive is how many times wider than a wi